INCORPORACIÓN DE LA ESPECTROMETRÍA DE LUZ VISIBLE COMO HERRAMIENTA ANALÍTICA PARA LA EVALUACIÓN DEL PORCENTAJE DE FERMENTACIÓN DEL CACAO EN GRANO (Theobroma Cacao) - VERA FRANCO, GENESIS PAOLA (2025)
The present study analyzes the evolution of pH and acidity during fermentation of two cocoa genotypes, CCN51 and EETP 800, using visible light spectrophotometry as an analytical tool